2014
DOI: 10.1007/s13753-014-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Temporal Population Distribution on Earthquake Loss Estimation: A Case Study on Sylhet, Bangladesh

Abstract: To estimate human loss in an earthquake-prone area, it is necessary to analyze the role played by the spatiotemporal distribution of the area's resident population. In order to evaluate earthquake impact, this article focuses on the spatiotemporal distribution of population and five scenario earthquakes that form the basis for loss estimation in the city of Sylhet, Bangladesh. Four temporal contexts (weekday, weekly holiday, the 30 days of Ramadan, and strike days) expand the more typical daytime and nighttime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Additionally, it is probable that the percentage of populations located outdoors is higher during working hours than during nighttime hours, especially in rural environments. These findings add to the growing volume of research stressing the importance of including temporal elements into natural-hazard studies (Chen et al, 2004;Ara, 2014;Aubrecht et al, 2012;Freire and Aubrecht, 2012;Guha-Sapir and Vos, 2011).…”
Section: Baseline Fatality Estimatesmentioning
confidence: 66%
See 3 more Smart Citations
“…Additionally, it is probable that the percentage of populations located outdoors is higher during working hours than during nighttime hours, especially in rural environments. These findings add to the growing volume of research stressing the importance of including temporal elements into natural-hazard studies (Chen et al, 2004;Ara, 2014;Aubrecht et al, 2012;Freire and Aubrecht, 2012;Guha-Sapir and Vos, 2011).…”
Section: Baseline Fatality Estimatesmentioning
confidence: 66%
“…Accurately mapping population exposure is an essential part of the risk analysis process for environmental hazards (Chen et al, 2004;Freire and Aubrecht, 2012;Aubrecht et al, 2012). The presence of Syrian refugees in southeast Turkey complicates this process, especially as it pertains to datasets commonly used in earthquake fatality estimations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicated that the description and mapping of population distribution are basic and indispensable steps for disaster management, shelter selection, and emergency evacuations. Furthermore, daytime population distribution and density in urban areas are very different from the nighttime situation (Ara 2014). Freire (2010) used a dasymetric mapping approach to refine population distribution in Portugal.…”
Section: Introductionmentioning
confidence: 99%